2021
DOI: 10.1093/advances/nmaa087
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Dose and Duration of Zinc Interventions on Risk Factors for Type 2 Diabetes and Cardiovascular Disease: A Systematic Review and Meta-Analysis

Abstract: No meta-analysis has examined the effect of dose and duration of zinc interventions on their impact on risk factors for type 2 diabetes (T2D) or cardiovascular disease (CVD). This study aimed first to compare the effects of zinc interventions dichotomized as low versus high dose (<25 mg/d and ≥25 mg/d, respectively) and short versus long duration (<12 wk and ≥12 wk, respectively) on risk factors for T2D and CVD. Second, it discusses the results from the low-dose and long-duration meta-analyses as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 85 publications
(56 reference statements)
9
53
0
Order By: Relevance
“…Another trial performed 30mg of zinc supplementation for 30 days in 28 obese women, found a reduction in serum insulin and HOMA-IR values [14] . Also our result come in line with 2 recent systematic reviews concluded that Zn supplementation improves insulin resistance in obese individuals [15,16] .The difference from finding of another trial [17] , might due to the severity of metabolic disturbances, the dose and type of supplementation .…”
Section: Effect On Glucose Control and Irsupporting
confidence: 90%
“…Another trial performed 30mg of zinc supplementation for 30 days in 28 obese women, found a reduction in serum insulin and HOMA-IR values [14] . Also our result come in line with 2 recent systematic reviews concluded that Zn supplementation improves insulin resistance in obese individuals [15,16] .The difference from finding of another trial [17] , might due to the severity of metabolic disturbances, the dose and type of supplementation .…”
Section: Effect On Glucose Control and Irsupporting
confidence: 90%
“…It is suggested that Zn deficiency could be associated with a defect in insulin secretion due to its insulin-like effects via inhibition of the glycogen-regulating enzyme GSK3, activation of post-receptor proteins Akt and PI3 kinase, and the reduction of cytokines IL-1b and NFĸB [ 35 ]. Furthermore, the reduction in the blood concentrations of Zn from these patients was linked with an increased urinary excretion of Zn [ 37 , 38 ]. Some studies demonstrated that Zn supplementation may provide an important protection against diabetes as complications of diabetes were highly linked with Zn deficiency [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the reasons of these discrepancies remain unresolved, dose and duration of zinc supplementation may affect the effect of zinc on the risk of CVDs. The latest recent meta-analysis revealed that low-dose zinc supplementation ( 25 mg/d) and long-duration (≥ 12 weeks) improved fasting blood glucose and serum lipids, including total cholesterol and LDL, more than high-dose (≥ 25 mg/d) and short-duration ( 12 weeks) interventions 112) . To determine the most effective dose and duration of zinc supplementation, further study seems to be necessary.…”
Section: -3 Zinc Transporters and Vascular Cell Functionmentioning
confidence: 99%